Mapping, evolution, and application trends in co-citation analysis: a scientometric approach - Robledo-Giraldo, Sebastian; Figueroa-Camargo, Jose Gregorio; Zuluaga-Rojas, Martha Viviana; Vélez-Escobar, Sol Beatriz; Duque- Hurtado, Pedro Luis (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This study aims to explore the mapping, evolution, and application trends of co-citation analysis. To accomplish this goal, a comprehensive search was conducted using Scopus and Web of Science, resulting in 1298 relevant studies. Further analysis was conducted on scientific production, country, author, journal, and network data. The Tree of Science algorithm was applied to demonstrate the development of co-citation analysis. The results make three significant contributions to scientometric research: Firstly, a scientific mapping is presented highlighting the scientific output, main journals, and key researchers; secondly, the advancements of co-citation analysis are presented through the Tree of Science metaphor; lastly, the study identifies the three main subtopics within co-citation analysis through citation analysis. These findings will assist researchers and librarians in recognizing the crucial contributions and applications of co-citation analysis.